Deep sequencing of myxoinflammatory fibroblastic sarcoma. Issue 5 (31st January 2020) - Arbajian, Elsa; Hofvander, Jakob; Magnusson, Linda; Mertens, Fredrik
Abstract: Myxoinflammatory fibroblastic sarcoma (MIFS) has recurrent genetic features in the form of a translocation t(1;10)(p22‐31;q24‐25), BRAF gene fusions, and/or an amplicon in 3p11‐12 including the VGLL3 gene. The breakpoints on chromosomes 1 and 10 in the t(1;10) cluster in or near the TGFBR3 and OGA genes, respectively. We here used a combination of deep sequencing of the genome (WGS), captured sequences (Cap‐seq), and transcriptome (RNA‐seq) and genomic arrays to investigate the molecular outcome of the t(1;10) and the VGLL3 amplicon, as well as to assess the spectrum of other recurrent genomic features in MIFS. Apart from a ROBO1 ‐ BRAF chimera in a t(1;10)‐negative MIFS‐like tumor, no fusion gene was found at RNA‐seq. This was in line with WGS and Cap‐seq results, revealing variable breakpoints in chromosomes 1 and 10 and genomic breakpoints that should not yield functional fusion transcripts. The most common genomic rearrangements were breakpoints in or around the OGA, NPM3, and FGF8 genes in chromosome band 10q24, and loss of 1p11‐p21 and 10q26‐qter (all simultaneously present in 6/7 MIFS); a breakpoint in or near TGFBR3 in chromosome 1 was found in four of these tumors. Amplification and overexpression of VGLL3 was a consistent feature in MIFS and MIFS‐like tumors with amplicons in 3p11‐12. The significant molecular genetic outcome of the recurrent t(1;10) could be loss of genetic material from 1p and 10q. Other recurrent genomic imbalances in MIFS, such as homozygous loss of CDKN2A and 3p‐ and 13q‐deletions, are shared with other sarcomas, suggesting overlapping pathogenetic pathways.